2004
DOI: 10.1097/01.sla.0000133185.23514.32
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Resection for Rectal Cancer With Mesorectal Excision

Abstract: Anterior resection with mesorectal excision is a safe option and can be performed in the majority of patients with rectal cancer. The local recurrence rate was 9.7% and the cancer-specific survival was 74.5%. When the tumor requires a TME, this procedure is more complex and has a higher leakage rate than in those higher tumors where PME provides adequate mesorectal clearance. By performing TME in patients with mid and distal rectal cancer, the local control and survival of these patients are similar to those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
281
2
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 429 publications
(319 citation statements)
references
References 23 publications
26
281
2
10
Order By: Relevance
“…These include tumour level within the rectum 20 -22 , tumour size 23 , macroscopic morphology 24 , distal clearance 3,22,25 , circumferential clearance 26 -28 , depth of tumour invasion 28 -31 , lymph node metastasis 21,23,26,29 -31 , number of involved nodes 25,32 , tumour stage 3,6,20,22,24,33 -35 , grade of differentiation 20,23,26,28,32 , infiltrating tumour margin 26 , vascular invasion 3,6,22,26 , sex 22 , age 25,31 , intraoperative spillage of tumour cells 6,20 , anastomotic leakage 22,34 , experience and specialization of the surgeon 6,20 , surgical technique 3,22,35 , interhospital variability 20 and adjuvant therapy 6,23,31,33 . However, an extensive literature search by the authors failed to find any publications in which the position of the tumour was considered as a possible risk factor for local recurrence, although in one study position was found to be associated with cancer-specific mortality 36 .…”
Section: Discussionmentioning
confidence: 99%
“…These include tumour level within the rectum 20 -22 , tumour size 23 , macroscopic morphology 24 , distal clearance 3,22,25 , circumferential clearance 26 -28 , depth of tumour invasion 28 -31 , lymph node metastasis 21,23,26,29 -31 , number of involved nodes 25,32 , tumour stage 3,6,20,22,24,33 -35 , grade of differentiation 20,23,26,28,32 , infiltrating tumour margin 26 , vascular invasion 3,6,22,26 , sex 22 , age 25,31 , intraoperative spillage of tumour cells 6,20 , anastomotic leakage 22,34 , experience and specialization of the surgeon 6,20 , surgical technique 3,22,35 , interhospital variability 20 and adjuvant therapy 6,23,31,33 . However, an extensive literature search by the authors failed to find any publications in which the position of the tumour was considered as a possible risk factor for local recurrence, although in one study position was found to be associated with cancer-specific mortality 36 .…”
Section: Discussionmentioning
confidence: 99%
“…21 PNI has been studied in many malignancies, including prostate cancer, head and neck cancer, and cancer in the gastrointestinal tract, 9,[22][23][24] yet there is still no agreement on a clear definition of PNI-positive. A stringent definition of PNI requires that tumor cells be observed inside the perineurial layer, 7 but this definition would not include the situation of tumor cells existing within epineurium.…”
Section: Discussionmentioning
confidence: 99%
“…1 The largest randomized trials of rectal cancer generally have used radical abdominal surgery with good results. [11][12][13][14] To our knowledge, there have not been large randomized trials comparing TAE and preoperative chemoradiotherapy to radical abdominal surgery. However, quality of life issues associated with radical abdominal …”
Section: Discussionmentioning
confidence: 99%